Pemanfaatan Sumber Belajar Dalam Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Miftahul Jannah (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
The use of various learning resources should be used by students to assist students in obtaining various information regarding learning. Learning resources play an important role in the efforts to solve problems encountered by students in the learning process. Learning resources that can be used for learning needs are of various types and forms. Learning resources can be in the form of people, materials, environment, learning tools and equipment, techniques and messages. With the procurement and use of various learning resources that are more varied by students, they can provide information in order to improve the quality of learning. If good learning quality is achieved, good learning outcomes will also be achieved. The widest possible use of learning resources is used by students for learning needs and efforts to get maximum learning outcomes, so these learning resources need to be developed and managed systematically, well and functionally. Thus learning resources provide a positive contribution in improving learning outcomes of elementary school students.